Maximizing Driving Range for Fuel Cell Range Extender Vehicles with Fixed Energy Storage Costs - Dong, Jingting (My University, 2022)
Industry and researchers are investigating both battery electric vehicles (BEVs) and fuel cell hybrid vehicles (FCHV) for the future of sustainable passenger vehicle technology. While BEVs have clear efficiency advantages, FCHVs have key benefits in terms of refueling time and energy density. This thesis first proposes the concept of a fuel cell range extended vehicle (FCREV) that uses Whole-Day Driving Prediction (WDDP) control, which uses driver destination inputs to determine whether the planned driving trips that day will exceed the useable battery energy capacity. If so, the fuel cell is turned on at the start of the day. The benefit of WDDP control is that a smaller, lower cost fuel cell can be used to greatly extend the driving range, since the fuel cell can charge the battery during both driving and parked periods of the day. Furthermore, this research proposes a fast analytical optimization algorithm for designing a WDDP-FCREV to maximize range on a given drive cycle for a set cost. The results show an optimized WDDP-FCREV can greatly exceed the range of a same-cost BEV, by 105% to 150% for no H2 refueling and by 150% to 250% when H2 refueling is allowed every 4 hours.
Keywords: fuel cells; modeling; optimization methods; vehicles